Fuzzy object-oriented databases model with hedge algebra based semantics. - Hào, Nguyễn Công; Lê, Trương Thị Mỹ (Journal of Computer Science and Cybernetics, 2012)
In recent times, fuzzy object-oriented databases model has been studied in many different approaches such as fuzzy set theory, possibility theory, ... However, the mentioned approach are still limited in data performance and matching. In this paper, we propose a new approach to overcome the limitations of the approach that is based on hedge algebra structure for building fuzzy object-oriented databases model. Some operators fuzzy object-oriented relation algebra are proposed corresponding with the model. Finally,we propose a method of fuzzy object-oriented query processing flexibly.